(untitled) (IUBAT Review, 2026)
Shifting cultivation, locally known as Jhum, is a traditional agricultural practice among the indigenous communities of the Rangamati Hill Tracts. Climate change—characterized by long-term shifts in temperature and weather patterns—poses increasing challenges to this system. Since agricultural productivity relies heavily on climatic factors such as temperature, rainfall, light intensity, radiation, and sunshine duration, the growing irregularity of these elements due to global warming threatens the stability of Jhum cultivation. This study examines the impacts of climate change on shifting cultivation and explores the adaptive strategies adopted by local farmers. Data were collected through field surveys, Focus Group Discussions (FGDs), and Key Informant Interviews (KIIs) with farmers and agricultural experts. Rainfall emerged as one of the most influential climatic factors, particularly because Jhum farming is rain-fed and highly sensitive to precipitation variability.Farmers have become increasingly aware of climate unpredictability and are adapting through crop diversification, adjusted planting calendars, improved water management, increased use of agricultural inputs, and tree planting. These strategies draw on community knowledge and help reduce environmental risks while promoting economic resilience. Strengthening such adaptive measures is crucial for sustainable development, minimizing losses from extreme weather events, and supporting long-term agricultural productivity in the region. IUBAT Review—A Multidisciplinary Academic Journal, 8(2): 154-175